Implementasi Pembinaan dan Pengawasan Untuk Meningkatkan Kapasitas Pengetahuan Industri Kecil Menengah di Kota Surabaya - Nafisa, Shella Alfiani; Nurjanti Takarini (Politeknik Piksi Ganesha Indonesia, 2025)
Coaching and supervision is one of the industrial work programs that includes information on evaluation, compliance records, and recommendations for improvement for industries that have been coached or supervised. This study aims to analyze the implementation and effectiveness of the implementation of the coaching and supervision program in Small and Medium Industries in Surabaya City. Data were analyzed using qualitative methods and descriptive approaches using interview techniques. The results of the interviews revealed that the program was effective in increasing SME understanding regarding business licensing and industry standards. However, there were also obstacles from the organizers in the form of limited human resources and differences of understanding among the beneficiaries. The results of the study indicate that synergistic efforts are needed between the Department of Industry and Manpower and SME actors to increase the effectiveness of the coaching and supervision program to further increase SME interest in complying with all existing regulations.